Sistem Monitoring Lahan Parkir berbasis Bluetooth Low Energy (BLE) - Muhammad Faza Ramadhana; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Vehicle mobility in urban areas or areas which are increasingly large, causing problems in the provision of parking lots. Information about parking slot availability is needed to overcome this problem. A monitoring system is required to inform motorists of empty parking locations. The monitoring system is one of the concepts of the Internet of things (IoT), which is a real-time observation system using an internet connection through a protocol. Bluetooth Low Energy (BLE) is a protocol that can be used for communication between devices that saves power, has a wide range of connectivity and reduces data transfer. Therefore, researchers conducted research by implementing BLE which is applied to the parking lot monitoring system. Based on the test results, it can be concluded that the ESP32 is able to communicate with each other using BLE technology. The sensor accuracy level obtained from ultrasonic sensor is 95.12% with an obstacle distance of 5cm to 400cm and an infrared sensor is able to read obstacles and work properly. On testing the delay in sending data based on a distance of 1 meter, 3 meters, 5 meters, 7 meters and 9 meters the average delay received was 2049.65 ms, 2086.25 ms, 2108.05 ms, 2449.15ms and 2612.77ms. The webserver display is able to display information about the availability of parking space and the number of cars entering and exiting.